Niat dan Perilaku Mahasiswa di Indonesia Untuk Bertransaksi Ziswaf Secara Digital Melalui Layanan M-Banking Syariah - Saibil, Defi Insani; Romadoni, Muhammad Fathul (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2023)
This research is to analyze the behavior and intentions of students to transact ZISWAF digitally through sharia m-banking services. This study uses the expansion of the Unified Theory of Acceptance and Use to Technology (UTAUT) model by adding the trust construct. Data collection used the Google form with a sample of students who had ZISWAF digitally through sharia m-banking with a sample of 97 respondents. The research findings show that the intention to participate in ZISWAF through sharia m-banking is influenced by social influence, facilitating conditions and trust. However, the variable performance expectations and effort expectations are not significant to behavioral intentions. Meanwhile, adoption behavior (usage adoption) is influenced by beliefs and behavioral intentions which significantly influence the adoption of sharia m-banking services for students with ZISWAF among students in Indonesia.